Pelatihan Pembuatan Penelitian Tindakan Kelas (PTK) bagi Guru-Guru Yayasan Pendidikan Mataram Semarang - Irene Hartutik; Dicky Aprianto; Nerita Setiyaningtiyas (Jurnal Pengabdian Kepada Masyarakat, 2024)
Classroom Action Research (CAR) is a way to enhance or enhance the quality of learning. The aim of this non-profit service is to provide training to Mataram Educatin Foundation teachers to conduct action research in the classroom to improve the quality of learning. The results of this non-profit service show how important it is for a teacher to stay on top of her PTK and motivate her students to improve their learning outcomes.